Comparison of antioxidant activity of extracts of hop leaves harvested in different years - Muzykiewicz Anna; Nowak Anna; Zielonka-Brzezicka Joanna; Florkowska Katarzyna; Duchnik Wiktoria; Klimowicz Adam (Herba Polonica, 2019)
Introduction: Hop (Humulus lupulus L.) is a common plant in Europe, with many beneficial health effects. In addition to the use in brewing, hops are a valuable source of active substances used in conventional and folk medicine, such as humulones and lupulones, as well as antioxidants, including phenolic compounds.